Preconcentration of valsartan by dispersive liquid–liquid microextraction based on solidification of floating organic drop and its determination in urine sample: Central composite design. Issue 10 (2nd May 2016) - Pebdani, Arezou Amiri; Shabani, Ali Mohammad Haji; Dadfarnia, Shayesteh; Talebianpoor, Mohammad Sharif; Khodadoust, Saeid
Abstract : In this work, a fast, easy, and efficient dispersive liquid–liquid microextraction method based on solidification of floating organic drop followed by high‐performance liquid chromatography with UV detection was developed for the separation/preconcentration and determination of the drug valsartan. Experimental design was applied for the optimization of the effective variables (such as volume of extracting and dispersing solvents, ionic strength, and pH) on the extraction efficiency of valsartan from urine samples. The optimized values were 250.0 μL ethanol, 65.0 μL 1‐dodecanol, 4.0% w/v NaCl, pH 3.8, 1.0 min extraction time, and 4.0 min centrifugation at 4000 rpm min −1 . The linear response ( r 2 = 0.997) was obtained in the range of 0.013–10.0 μg mL −1 with a limit of detection of 4.0 ng mL −1 and relative standard deviations of less than 5.0 % ( n = 6).